Screening of Human Circular RNAs as Biomarkers for Early Onset Detection of Alzheimer’s Disease - Zheng, Da; Tahir, Rana Adnan; Yan, Yan; Zhao, Juan; Quan, Zhenzhen; Kang, Guixia; Han, Ying; Qing, Hong (Frontiers in Neuroscience, 2022)
Circular RNAs (circRNAs) are a distinctive type of endogenous non-coding RNAs, and their regulatory roles in neurological disorders have received immense attention. CircRNAs significantly contribute to the regulation of gene expression and progression of neurodegenerative disorders including Alzheimer’s disease. The current study aimed to identify circRNAs as prognostic and potential biomarkers in Alzheimer’s disease. The differentially expressed circRNAs among subjective cognitive decline, amnestic mild cognitive impairment, and age-matched normal donors were determined through Arraystar Human circRNA Array V2 analysis. The annotations of circRNAs-microRNA interactions were predicted by employing Arraystar’s homemade miRNA target prediction tool. Bioinformatics analyses comprising gene ontology enrichment, KEGG pathway, and network analysis were conducted. Microarray analysis revealed the thirty-three upregulated and eleven downregulated differentially expressed circRNAs (FC ≥ 1.5 and p-values ≤ 0.05). The top 10 differentially expressed upregulated and downregulated circRNAs have been chosen for further expression validation through quantitative real-time PCR and subsequently, hsa-circRNA_001481 and hsa_circRNA_000479 were confirmed experimentally. Bioinformatics analyses determined the circRNA-miRNA-mRNA interactions and microRNA response elements to inhibit the expression of miRNAs and mRNA targets. Gene ontology enrichment and KEGG pathways analysis revealed the functional clustering of target mRNAs suggesting the functional verification of these two promising circRNAs. It is concluded that human circRNA_001481 and circRNA_000479 could be utilized as potential biomarkers for the early onset detection of Alzheimer’s disease and the development of effective therapeutics.